Air temperature triggers the recovery of evergreen boreal forest photosynthesis in spring - Suni Tanja; Frank Berninger; Timo Vesala; Tiina Markkanen; Pertti Hari; Annikki Mäkelä; Hannu Ilvesniemi; Heikki Hänninen; Eero Nikinmaa; Timo Huttula; Tuomas Laurila; Mika Aurela; et al. (Global Change Biology, 2003)
The timing of the commencement of photosynthesis ( P * ) in spring is an important determinant of growing‐season length and thus of the productivity of boreal forests. Although controlled experiments have shed light on environmental mechanisms triggering release from photoinhibition after winter, quantitative research for trees growing naturally in the field is scarce. In this study, we investigated the environmental cues initiating the spring recovery of boreal coniferous forest ecosystems under field conditions. We used meteorological data and above‐canopy eddy covariance measurements of the net ecosystem CO 2 exchange ( NEE ) from five field stations located in northern and southern Finland, northern and southern Sweden, and central Siberia. The within‐ and intersite variability for P * was large, 30–60 days. Of the different climate variables examined, air temperature emerged as the best predictor for P * in spring. We also found that ‘soil thaw’, defined as the time when near‐surface soil temperature rapidly increases above 0°C, is not a useful criterion for P * . In one case, photosynthesis commenced 1.5 months before soil temperatures increased significantly above 0°C. At most sites, we were able to determine a threshold for air‐temperature‐related variables, the exceeding of which was required for P * . A 5‐day running‐average temperature ( T 5 ) produced the best predictions, but a developmental‐stage model ( S ) utilizing a modified temperature sum concept also worked well. But for both T 5 and S , the threshold values varied from site to site, perhaps reflecting genetic differences among the stands or climate‐induced differences in the physiological state of trees in late winter/early spring. Only at the warmest site, in southern Sweden, could we obtain no threshold values for T 5 or S that could predict P * reliably. This suggests that although air temperature appears to be a good predictor for P * at high latitudes, there may be no unifying ecophysiological relationship applicable across the entire boreal zone.

Microbial characteristics of soils on a latitudinal transect in Siberia - HANA ŠANTRU˚CˇKOVÁ; MICHAEL I. BIRD; YEVGENIY N. KALASCHNIKOV; MILAN GRUND; DANA ELHOTTOVÁ; MILOSLAV ŠIMEK; SERGEY GRIGORYEV; GERD GLEIXNER; ALMUT ARNETH; ERNST‐DETLEF SCHULZE; JON LLOYD (Global Change Biology, 2003)
Soil microbial properties were studied from localities on a transect along the Yenisei River, Central Siberia. The 1000 km‐long transect, from 56°N to 68°N, passed through tundra, taiga and pine forest characteristic of Northern Russia. Soil microbial properties were characterized by dehydrogenase activity, microbial biomass, composition of microbial community (PLFAs), respiration rates, denitrification and N mineralization rates. Relationships between vegetation, latitude, soil quality (pH, texture), soil organic carbon (SOC) and the microbial properties were examined using multivariate analysis. In addition, the temperature responses of microbial growth (net growth rate) and activity (soil respiration rate) were tested by laboratory experiments. The major conclusions of the study are as follows: 1. Multivariate analysis of the data revealed significant differences in microbial activity. SOC clay content was positively related to clay content. Soil texture and SOC exhibited the dominant effect on soil microbial parameters, while the vegetation and climatic effects (expressed as a function of latitude) were weaker but still significant. The effect of vegetation cover is linked to SOC quality, which can control soil microbial activity. 2. When compared to fine‐textured soils, coarse‐textured soils have (i) proportionally more SOC bound in microbial biomass, which might result in higher susceptibility of SOC transformation to fluctuation of environmental factors, and (ii) low mineralization potential, but with a substantial part of the consumed C being transformed to microbial products. 3. The soil microbial community from the northernmost study region located within the permafrost zone appears to be adapted to cold conditions. As a result, microbial net growth rate became negative when temperature rose above 5 °C and C mineralization then exceeded C accumulation.